2020
DOI: 10.1002/job.2433
|View full text |Cite|
|
Sign up to set email alerts
|

Putting time in perspective: How and why construal level buffers the relationship between wait time and aggressive tendencies

Abstract: Summary We spend a substantial part of our daily life waiting, and unfortunately, wait time can fuel aggressive tendencies. Our study examines the relationship between wait time, perceived wait time, and aggressive tendencies from a construal level perspective. In Study 1, we found that the higher the construal level, the stronger the relationship between actual and perceived wait time and the stronger relationship between perceived wait time and aggressive tendencies. In Study 2, we manipulated construal leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 109 publications
0
18
0
Order By: Relevance
“…Finally, Efrat‐Treister, Daniels, and Robinson () investigate how temporal construal impacts employee perceptions of waiting as well as aggressive response tendencies following waiting. Here, time perspective is addressed by understanding temporal construal in its abstract (high construal) versus concrete (low construal) levels.…”
Section: Articles In the Special Issuementioning
confidence: 99%
“…Finally, Efrat‐Treister, Daniels, and Robinson () investigate how temporal construal impacts employee perceptions of waiting as well as aggressive response tendencies following waiting. Here, time perspective is addressed by understanding temporal construal in its abstract (high construal) versus concrete (low construal) levels.…”
Section: Articles In the Special Issuementioning
confidence: 99%
“…Other scholars suggested that the negative affectivity of health consumers or their families (caused by a variety of reasons) is directly related to aggressive tendencies in the hospital setting [ 63 , 64 ]. We define aggressive tendencies following [ 65 ] as the self-reported desire to act with aggression. We chose this focus since the desire to act with aggression is an important predictor of actual aggressive behavior [ 65 ], and as such, it is important to curtail this desire before it escalates into actual aggression.…”
Section: Introductionmentioning
confidence: 99%
“…We define aggressive tendencies following [ 65 ] as the self-reported desire to act with aggression. We chose this focus since the desire to act with aggression is an important predictor of actual aggressive behavior [ 65 ], and as such, it is important to curtail this desire before it escalates into actual aggression. Aggressive tendencies can be expressed in a variety of forms, from interpersonal conflict to bullying or even physical assault [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive tendencies were de ned as the self-reported desire to act with aggression (65).The measure of aggressive tendencies was based on (72), focusing on four aggressive tendencies that t the context of the large variety of wards in which the medical clowns performed. Speci cally, we asked participants to evaluate the likelihood that in the near future someone in their ward will curse the medical staff's family, vandalize hospital property, bang on a table, or complain about medical staff.…”
Section: Methodsmentioning
confidence: 99%